(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the formation of competence of student in high protsnsse learning the basic of geography and economics. The essence and structure a concept of "competence". Proved that the implementation of competency is determind high school students to demonstrate how the knowledge. Transformation and synthese knowledge that form the natural and social scence world picture.